Claude Coste, Sylvie Douche, Barthes et la musique (Altre Modernità, 2020)
Claude Coste, Sylvie Douche, Barthes et la musique(Rennes, PUR, 2018, 362 pp. ISBN 978-2-7535-7545-5)par Maria Chiara Brandolini